Estimation of the mechanical properties for bone – titanium biocomposite based on computed tomography data and finite element modeling - Nikitsin, Andrei V. (Journal of the Belarusian State University. Mathematics and Informatics, 2020)
The goal of this work is to study the effect of bone ingrowth into open pores of the implant and estimate of the mechanical characteristics for obtained biocomposite. Reconstruction of the isotropic model based on data acquired from computed tomography allows us to study the metallic and bone components integration under compressive load. Results are compared to performed mechanical tests of the porous specimen. The finite element modeling allows obtaining a stress-stain curve for the bone – titanium biocomposite. Young’s modulus of the metallic specimen is increased by 29 % after pores is filled with bone tissues. The conditional yield strength of the bone – titanium biocomposite is 2 times higher than that of porous open-pore titanium.
Keywords: finite element analysis; osteointegration; computed tomography; porous structure